Multitechnique Experimental Insight on an Unusual Crystal-to-Crystal High Temperature Solid State Reaction in Zirconium Carboxypyridinephosphonates: From One-Dimensional Chains to Two-Dimensional Hybrid Layers Through HF Elimination - Marco Taddei (Crystal Growth & Design, 2012)
Two novel N-phosphonoethylcarboxypyridines were prepared via nucleophilic substitution of two carboxypyridines (namely, 4-carboxypyridine, or isonicotinic acid, and 3-carboxypyridine, or nicotinic acid) with diethyl-2-bromoethylphosphonate in water. Two zirconium derivatives of these acids were obtained under mild solvothermal conditions, and their structures were solved from powder X-ray diffraction (PXRD) data. The zirconium derivative containing the isonicotinic moiety (1), with formula ZrF2(HF)(O3PCH2CH2NC5H4CO2), has a one-dimensional (1D) chain structure in which the carboxypyridine groups are placed in the external part of the inorganic chain constituted of zirconium octahedra and phosphonic tetrahedra, whereas the zirconium derivative containing the nicotinic moiety (2), with formula ZrF2(O3PCH2CH2NC5H4CO2), has a hybrid layered structure in which zirconium octhaedra and phosphorus tetrahedra form a new structural archetype, with a C–O group coordinating the zirconium atoms. 1 underwent a high temperature (280 °C) slow solid state transformation that involved the loss of one HF molecule coordinated to the zirconium atom and the replacement of this coordination vacancy with the neighboring C–O– group belonging to the adjacent chain. The structure of this heated compound (1a) is a polymorph of 2. A multitechnique approach, based on coupled Fourier transform infrared spectroscopy and Raman and solid state NMR spectroscopy allowed us to carry out a thorough characterization of these materials, finding nice agreements on the chemical details of this solid state reaction.